Class Actions: Objectives, Experiences and Reforms (Final Report) - Kalajdzic, Jasminka; Piché, Catherine; Thomas, Nye; Carnerie, Fran; Lindsay, Susan; Vulimiri, Amita (2019)
In 2017, the Law Commission of Ontario (LCO) initiated an independent study to consider Ontario’s experience with class actions since the enactment of the Class Proceedings Act, 1992 (CPA). During this period, class actions have grown significantly in volume, complexity, and impact in Ontario and across Canada. Class actions also have systemic implications for access to justice, court procedures and efficiency, and government and corporate liability. Finally, this form of litigation has had major financial, policy and even cultural implications across the country.Following an intensive 18-month research project that included over 100 interviews with stakeholders and an empirical examination of Ontario cases, the LCO published its final report, and made over 40 recommendations for amendment and reform of the CPA. It is the first review of the CPA since the Act's inception, and the most detailed examination of class actions in Canada in three decades.
Keywords: Jasminka Kalajdzic